Site Specific Effect of Tobacco Addiction in Upper Aerodigestive Tract Tumors: A Retrospective Clinicopathological Study - Ashok Kumar; Amita Sharma; Babita Ahlawat; Sonam Sharma (The Scientific World Journal)
An institutional study was carried out in 102 patients to investigate the site specific effect of addictions, that is, tobacco smoking and tobacco chewing (smokeless), both independently and synergistically in development of malignancies in upper aerodigestive tract through retrograde questionnaire. The histopathologically proven cases were interviewed regarding different forms of addictions followed by clinical examination and investigations for grading (according to Modified Broadmann’s method) and TNM staging (according to UICC) according to the tumor site. Statistical analysis was done by Pearson test. Out of all proven cases of cancers, 29.4% were only tobacco chewers (smokeless), 25.5% were only smokers, 42.2% were having both types of tobacco addictions (smoke and smokeless), and only 2.9% were having no addiction. Out of only tobacco chewers (smokeless), 83.3% were of oral cavity cancers, 6.7% were of oro- and hypopharynx and the rest were of others. Among only smokers, 69.2% cases were of laryngeal and oro- and hypopharynx as compared to 11.5% of oral cavity cancers (nearly 6 times). Tobacco (smokeless) chewing is associated with oral cancers whereas tobacco smoking is associated with laryngeal and hypopharyngeal carcinoma. Both smoking and smokeless tobacco act in synergy with each other.